PENGARUH SUKU BUNGA DAN NILAI TUKAR TERHADAP HARGA SAHAM PT. BANK RAKYAT INDONESIA (PERSERO) DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Nany Karlina Nehe (Universitas Nias Raya, 2026)
The purpose of this study is to ascertain how interest and currency rates affect the price of PT shares. From 2017 to 2021, Bank Rakyat Indonesia (Persero) was listed on the Indonesian Stock Exchange. Associative quantitative research is the methodology employed. Multiple linear regression analysis is the data analysis method employed. The study's findings demonstrate the impact of interest and currency rates on stock prices. Moreover, a multiple linear regression analysis equation was derived for this study, which reads as follows: Y = 6,416,190 + (–2,771)X1 + (–419,382)X2, where 6,416,190 is the constant value. This indicates that the share price (Y) is 6,416.190 if the interest rate (X1) and exchange rate (X2) variables are zero. Regression coefficient (X1) for interest rates is -2.771. Assuming the other independent variables remain constant, this indicates that the share price variable (Y) will decline by -2.771 if the interest rate (X1) rises by one unit, or 100%. Interest rates and stock prices are impacted by this negative influence.